Relationship between Thinking Styles and Higher Order Thinking Skills - Asma Mumtaz; Ramat Ullah Bhatti; William Bart (National University of Modern Languages (NUML), Islamabad, 2021)
Thinking styles of students and higher order thinking skills are important aspects of teaching and learning process. The purpose of this study was to investigate the relationship between thinking styles and higher order thinking skills (HOTS) of secondary school students and also to find the gender-wise difference in the nature of this relationship. The population of this study was male and female chemistry students of grade 9 in Tehsil Rawalpindi. Random sampling technique was used to select the sample. The data were obtained using the Convergent and Divergent Test and Achievement Test of Chemistry; developed in the light of Bloom Taxonomy. A quantitative research method was used for collection, interpretation and analysis of data. According to results, the relationship between convergent thinking style and higher order thinking skills of students was negligible. However, the strength of this correlation between divergent thinking style and higher order thinking skills of students is positive. Therefore, the understanding of student's thinking styles can serve as initial guide in developing more effective and conductive teaching and learning environment for mastering higher order thinking skills (HOTS).